Study of PVDF Based Electrode Structure in Supercapacitors - Parulekar, Samata; Sholapure R, Shahbaz; Holmukhe, M.; B. Karandikar, P. (International Journal of Engineering and Technology, 2018)
Because of increasing demand there is a need for energy storage.Supercapacitor the new age energy storage device which can provide quick burst of energy. The study focuses on use of Polyvinylidene fluoride as the binder material in making of electrodes for supercapacitors. Polyvinylidene fluoride (PVDF) is a highly non-reactive thermoplastic fluoropolymer produced by the polymerization of vinylidene difluoride. It is a strong piezoelectric element. Piezoelectric effect is useful for generation of high voltages. Binder materials are responsible for holding the active material particles within the electrode. The study was focused on use of PVDF in Electric Double Layer Capacitors (EDLC) and Pseudo capacitors. In case of Electric Double Layer Capacitors the PVDF is used as binder material with activated carbon as electrode material. In case of Pseudo capacitor the PVDF is used as a binder material with activated carbon and metal oxide as electrode material. Research was performed with preparation of electrodes using 6 types of Activated carbons namely Vulcun XC 72, Pica, RP20, C60, NORIT and Graphene for different compositions. The test was conducted on single electrode and it was initially charged at a voltage of 2.2V and its discharge was recorded for a time period of 3 minutes. The research focuses on the material which is giving the best results in regarding to the key parameters of supercapacitors and also concentrates on the composition of Polyvinylidene fluoride (PVDF) which gives the highest value of capacitance with the lowest value of Equivalent series resistance in making electrodes for supercapacitors. Â Â